Pembelajaran IPS Terintegrasi Pendidikan Perdamaian Berbasis Local Wisdom Pela Gandong - Anju Nofarof Hasudungan (Institut Agama Islam Negeri Jember, 2020)
Abstract The post-conflict recovery effort in Ambon, Maluku, which it was the largest civil conflict after the collapse of the New Order, it was not only needed by the survivors of the conflict. But also by the generation that did not experience the bloody conflict. Like students in SMPN 9 Ambon City and SMPN 4 Salahutu Liang Central Maluku who are the next generation of Maluku and of course who will maintain Ambon peace in the future. In addition, the emergence of identity politics and populism that occurred during the General Election of the President and Vice President of the Republic of Indonesia for the 2014-2019 and 2019-2024 periods has become a serious threat to peace in Ambon City. The purpose of this research is to describe how social science education integrated the value of peace education based on local wisdom pela gandong. The research method uses descriptive qualitative case study approach. Data collection was carried out by means of literature study, interviews, participatory observation, and document analysis. The results showed, with the existence of social conflict material in social science education which was then integrated with Ambon conflict material and peace education based on pela gandong. Thus, students have improved both in terms of knowledge, skills and attitudes in understanding conflict and peace education through social science education. At the same time cut off the trauma, mutual suspicion and hatred experienced by students so far. Abstrak Upaya pemulihan pascakonflik di Ambon, Maluku, yang merupakan konflik sipil terbesar pasca runtuhnya Orde Baru, tidak hanya dibutuhkan oleh para penyintas konflik. Tetapi juga oleh generasi yang tidak mengalami konflik berdarah. Seperti siswa-siswi di SMPN 9 Kota Ambon dan SMPN 4 Salahutu Liang Maluku Tengah yang merupakan generasi penerus Maluku dan tentunya yang akan menjaga perdamaian Ambon di masa depan. Selain itu, munculnya politik identitas dan populisme yang terjadi pada Pemilihan Umum Presiden dan Wakil Presiden Republik Indonesia periode 2014-2019 dan 2019-2024 telah menjadi ancaman serius bagi perdamaian di Kota Ambon. Tujuan penelitian ini adalah mendeskripsikan bagaimana Ilmu Pengetahuan Sosial mengintegrasikan nilai pendidikan perdamaian berbasis kearifan lokal pela gandong. Metode penelitian menggunakan pendekatan studi kasus deskriptif kualitatif. Pengumpulan data dilakukan dengan studi pustaka, wawancara, observasi partisipatif, dan analisis dokumen. Hasil penelitian menunjukkan, dengan adanya materi konflik sosial dalam Ilmu Pengetahuan Sosial yang kemudian diintegrasikan dengan materi konflik Ambon dan pendidikan perdamaian berbasis pela gandong. Hasilnya, siswa mengalami peningkatan baik dari segi pengetahuan, keterampilan dan sikap dalam memahami konflik dan pendidikan perdamaian melalui Ilmu Pengetahuan Sosial. Sekaligus memutus trauma, saling curiga dan kebencian yang dialami siswa selama ini. Kata kunci: Ilmu Pengetahuan Sosial; Local Wisdom; Pela Gandong; Pendidikan Perdamaian